Place perception and restorative experience of recreationists in the natural environment of rural tourism - Tang, Ruomei; Zhao, Xinyu; Guo, Zixi (Frontiers in Psychology, 2024)
Introduction In contemporary society, people spend long periods under high stress, and tourism activities have gradually been internalized as a new means of stress release and self-recovery. Studies have found that the high-quality natural environment of rural tourism destinations has a higher restorative effect than other places, and the rural natural environment can provide psychological recovery to visitors on top of offering visual beauty and other experiences. Methods This paper starts with the relationship between rural place perception and restorative experience evaluation. Based on theories such as the restorative environments theory, we investigates whether rural natural environmental factors have a restorative effect on recreationists through collecting 300 questionnaires and using SPSS 26.0 structural equation modeling for analysis. Results The study found that there is a positive correlation between rural natural perception, place dependence, and restorative experience, forming a positive feedback loop dynamic system. The analysis suggests that enhancing the perception of the rural natural environment and place attachment can improve the restorative experience of recreationists in rural settings. Discussion This research establishes a systematic research framework for the relationship between rural natural perception, place attachment, and restorative experience, to deeply understand the dynamic interaction between them. It reveals the relationship between rural natural perception and restorative experience, suggesting that enriching the perceptual elements in rural natural spaces can meet the diverse needs of recreationists, enhance the sense of dependence and identification with rural spaces, and thus promote the psychological well-being and restorative experience of recreationists. The study also finds that place dependence plays a mediating role between rural natural perception and restorative experience. Place attachment and place identity, as mediating variables, act as bridges and catalysts in the process of rural natural perception affecting restorative experience.